Membership in Virtual Social Networks and Activity in Non-virtual Public Sphere (With Emphasis on Governmental Universities Students in Tehran) - esmaeil aalizad; Nazgol Ebrahim Tari (مطالعات رسانه‌های نوین, 2017)
Public sphere is the real field of emergence and continuity of social communications, institutions, and civil associations. Mass Medias, especially virtual social networks. Are among social phenomena which have close relationship with public sphere. In contemporary world, the result of the activities and experiences of the members of a society in virtual social networks, as a social determinant, can change the domain of the public sphere. This research concentrates on this relation, and in other word, it is a probe to answer the question that “can the virtual social networks strengthen the ability of social actors on non-virtual public sphere?” This research is applied, quantitative and explanatory, the logic of it is deduction, and its method is survey. The theoretical focus of the research is on the ideas of Hannah Arendt, Jurgen Habermas and recent standpoints in the field of public sphere and media. Studied population are students of Tehran universities in 2015-16. Sampling population of this research are 310 students and the sampling method is multi- instance probability. These two statement are the most important empirical findings of the research: First, the membership in few virtual social networks or too many of them doesn’t have any determinant role in the quantity of activity in non-virtual public sphere (civil associations). Second, activity in non-virtual public sphere decreases along with the increasing in the quantity of student’s activity in virtual social networks.